EKONOMI ISLAM DAN POLITIK HUKUM DI INDONESIA (Mazahib, 2013)
This paper will elaborate on the history of modern Islamic economic and political relationship with the law in an attempt to formulate a variety of Islamic economics Law. This article also describes the  position of Islamic economic in the Indonesian legal system so that it will be obtained a description of how an implementation of Islamic economic in the Indonesian economy. This picture is quite important to know to look atbase for development of Islamic economic laws existing in the two periods, the New Order and Reform Era.